Polymer coatings : technologies and applications - Parameswaranpillai, Jyotishkumar; Rangappa, Sanjay Mavinkere; Siengchin, Suchart (Boca Raton, FL : CRC Press, 2021)
"This book provides a comprehensive account of recent developments in polymer coatings, encompassing novel methods, techniques, and a broad spectrum of applications. Chapters explore key aspects of polymer coatings, highlighting fundamental research, different types, and technology advances. It also integrates various aspects of these materials from synthesis to application. Current status, trends, future directions, and opportunities are also discussed. With contributions from top international researchers from industry, academia, government, and private research institutions, new and experienced readers will benefit from this applications-oriented book"--
Polymer coating methods / Dr. Raj Kumar Arya -- Polymer coatings based on nanocomposites / Dr. Alfonso Pérez -- Mechanism, anti-corrosion protection and components of anti-corrosion polymer coatings / (Dr). Akarsh Verma.
OCLC-licensed vendor bibliographic record.
Keywords: Coating processes; Plastic coating; Polymers -- Industrial applications; TECHNOLOGY / Textiles & Polymers; TECHNOLOGY / Material Science